Egg Saver - Mohd Yusof, Muhammad Danish Imran; Khalid, Thaqif Aiman; Sulaini, Ammar Sufi; Basharie, Siti Mariam (Multidisciplinary Applied Research and Innovation, 2025)
Eggs left on the ground for extended periods are prone to contamination due to environmental factors and poor ergonomics. This project presents Egg Saver, an egg collecting machine that facilitate in collecting the floor eggs in poultry farming. The Egg Saver, powered by an ESP32 microcontroller Arduino system, uses a 12V motor to perform all movements and a gripping mechanism to transfer eggs to a designated storage area, improving operational efficiency. It is controllable via the Blynk app, enhancing user convenience. Capable of travelling at 0.1 m/s to 0.3 m/s on flat surfaces, the system can collect eggs within approximately one minute. With some improvement in the future, the Egg Saver demonstrates significant capability in helping Malaysia’s poultry farming sector.